Phenalenone-photodynamic therapy induces apoptosis on human tumor cells mediated by caspase-8 and p38-MAPK activation - Salmeron Pena, Maria Luisa; Quintana-Aguiar, Jose; De la Rosa, Juan V.; Lopez-Blanco, Felix; Castrillo, Antonio; Gallardo, German; Tabraue, Carlos (My University, 2018)
Photodynamic therapy (PDT) is a rising and hopeful treatment for solid tumors and others malignancies. PDT uses harmless visible light to activate a tumor-associated photosensitizer (PS). The excited PS generates cytotoxic reactive oxygen species (ROS) that induce damage and death of tumor cells. It is known that certain phytoalexins and phytoanticipins derived from plants often display a PS-like activity due to a phenalenone (PN) moietyan efficient singlet oxygen photosensitizerin its skeleton. The aim of this study is to explore the phototoxic properties of PN on the human cell line tumor-derived HL60 (acute promyelocytic leukemia) and to identify the cell-specific targets of ROS involved in the tumor cell death. Our results reveal that PN acts as an excellent PS, showing a potent antitumor cell activity in presence of light. PN-PDT generates intracellular ROS, via oxidation reaction mechanisms type I and II, resulting in an induction of apoptosis. Moreover, both extrinsic (through direct activation of caspase-3) and intrinsic (through mitochondrial depolarization) pathways of apoptosis are induced by PN-PDT. Using pharmacologic inhibitors, we also find that PN-PDT activates caspase-8/tBid and p38-MAPK, triggering the activation of the apoptotic pathways. Although, survival pathways are also promoted through PI3K/Akt and JNK activation, the net result of PN-PDT is the tumor cell death. The present work identifies to PN, for the first time, as a potent photosensitizer in human tumor cell lines and proposes a mechanism by which ROS induces apoptosis of tumor cell.
Keywords: apoptosis; phenalenone; photodynamic therapy; ros; tumor cell